HISTORIOGRAPHY OF THE FORMATION OF HISTORICAL KNOWLEDGE IN CENTRAL ASIA - Mamanov Jamal Khudayberdievich (TADQIQOTLAR.UZ, 2024)
Abstract: In the history of mankind, the stone age included the longest period, during which progress was developed step by step, that is, in an evolutionary way. Only by the New Stone Age, drastic changes occur in human society. This process was observed in Mesopotamia and Egypt from the 7 th millennium BC, in India, Iran and the south of Central Asia from the 6 th millennium BC. For millions of years, people lived only using the gifts of nature, that is, eating fruits and vegetables grown in nature and meat products obtained as a result of hunting in their daily life. This article provides information about the history of the emergence and formation of historical knowledge in Central Asia.